Influência da afetividade no desenvolvimento cognitivo de alunos do ensino infantil e ensino fundamental: uma revisão bibliográfica - Silva, Pedro Marques da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In many ways, the teacher-student relationship can be very influential in the teaching and learning process, and the way in which this relationship occurs can result in good or bad academic development for the student. However, this is one of the factors that affect the students' school life, but there are also internal and external, intra and extra personal factors that act at the same time, all interfering in the results that these students will have at school. Based on the foregoing, the role of the teacher is very important as he assumes several functions to which the students' lives are linked. The teacher can be the emotional support of some, interfere in the relationships of friendships and enmities that occur between students, how he influences the student's life and also the view of himself. Through all this mentioned subject, we can assess this through affectivity, positive and negative, and see how it is intrinsically related to the cognitive development of students. Thus, in order to debate this relationship between affectivity and the cognitive development of students, the present work is a bibliographical survey to analyze and discuss this theme. For this, the bibliographic search was performed in the SciELO databases - Scientific Electronic Library Online, Brazilian Digital Library of Theses and Dissertations - BDTD, CAPES Periodicals and Academic Google, using the keywords: academic performance, interpersonal relationships, cognition and affection. After searching and applying the pre-established inclusion and exclusion criteria, 1 article was found in the CAPES platform, 17 in the SciELO platform, 4 works in the BDTD and 20 articles in Academic Google, totaling 42 articles that were analyzed. The results indicate that the affective relationship and dialogue for a healthy cognitive development for students is undeniable. However, this emotional intelligence is still lacking in the school environment, and even with research in the area, it is still a new theme and with many difficulties to be inserted and carried out in the school environment.

A relação professor- aluno pode ser de diversas formas muito influente no processo de ensino e aprendizagem, e o modo como essa relação ocorre pode acarretar em um bom, ou ruim, desenvolvimento acadêmico do aluno. Porém esse é um dos fatores que acometem a vida escolar dos alunos, mas também há fatores internos e externos, intra e extra pessoais que agem ao mesmo tempo, todos interferindo no resultado que esses alunos terão na escola. Mediante o exposto, o papel do professor é muito importante pois ele assume várias funções ao qual está vinculado a vida dos alunos. O professor pode ser o apoio emocional de alguns, interferir nas relações de amizades e inimizades que ocorrem entre os alunos, como ele influencia na vida do aluno e também a visão de si mesmo. Mediante a todo esse assunto mencionado, podemos avaliar isso através da afetividade, positiva e negativa, e constatar como ela está intrinsecamente relacionada ao desenvolvimento cognitivo dos alunos. Assim, para debater essa relação da afetividade e o desenvolvimento cognitivo dos alunos, o presente trabalho se trata de levantamento bibliográfico para analisar e discutir essa temática. Para isso, a pesquisa bibliográfica foi executada nos bancos de dados SciELO - Scientific Electronic Library Online, Biblioteca Digital Brasileira de Teses e Dissertações – BDTD, Periódicos da CAPES e Google Acadêmico, utilizando as palavras-chaves: rendimento escolar, relações interpessoais, cognição e afetividade. Após a busca e a aplicação dos critérios de inclusão e exclusão pré-estabelecidos foram encontrados 1 artigo na plataforma CAPES, 17 na plataforma SciELO, 4 trabalhos na BDTD e 20 artigos no Google Acadêmico, totalizando 42 artigos que foram analisados. Os resultados indicam que é inegável a relação afetiva e o diálogo para um desenvolvimento cognitivo sadio para os alunos. Todavia essa inteligência emocional ainda é faltante no meio escolar, e mesmo com pesquisas nas áreas, ainda é uma temática nova e com muitas dificuldade para ser inserida e feita no âmbito escolar.
Influence of affectivity on cognitive development of students childhood education and elementary education: a literature review
Keywords: Affectivity; Interpersonal relationships; Cognition; School performance; Afetividade; Cognição; Ensino; Relações interpessoais; Rendimento escolar